Penggunaan Akta Konsen Roya Akibat Sertifikat Hak Tanggungan Yang Hilang Pada Kantor Pertanahan Kabupaten Asahan - Fakhri Bahira Ibtihaj Lubis; Ahmad Fauzi; Ruslan Ruslan (Mahesa Research Center, 2023)
This study aims to determine the authority of notaries and Land Deed Making Officials (PPAT) in making a concession agreement deed due to a lost mortgage certificate, analyzing the stages and processes in registering a concession agreement deed due to a lost mortgage certificate at the Asahan Regency Land Office and assessing the position law and the use of a concession agreement deed due to a lost mortgage certificate at the Asahan Regency Land Office. This study uses a qualitative descriptive method with a case approach and a statutory approach. The results of the study indicate that the Royal Consent Deed was made with a notarial deed. Although the APHT, which is the